Gaya Kepemimpinan Kepala KUA dan Kualitas Pelayanan Keagamaan di Padang Utara - Alfindo Ananta; Melati Jafari; Syamsir .; Amelia Putri; Cahaya Benardo; Allysa Rahma Safira; Raina Tshalasha; Vhaiz Alfarisy de Rekha (Jurnal Ilmu Sosial, Humaniora dan Seni, 2026)
The Head of the Office of Religious Affairs (KUA) as a leader of a public service institution is expected to improve the quality of religious services amid various constraints, including limited human resources and inadequate facilities. Without an appropriate leadership style, the quality of public services is difficult to improve optimally. This study aims to analyze the leadership style of the Head of KUA in Padang Utara District in efforts to improve the quality of religious services for the community. This study employs a qualitative approach with a descriptive method. Data were collected through in-depth interviews, direct observation, and documentation studies. The analysis technique used is data reduction, data presentation, and conclusion drawing based on the Miles and Huberman interactive analysis model. The findings indicate that the Head of KUA in Padang Utara District applies a combination of transformational and participative leadership styles. This approach has proven effective in improving employee discipline and responsiveness in service delivery. Service quality is also supported by effective communication between the leader and employees, as well as well-maintained work motivation. However, services still face challenges in the form of limited staff and inadequate facilities. As improvement measures, the leader strengthens internal coordination, conducts routine employee development, provides training, and utilizes information technology in the service process. Thus, effective leadership is proven to be a key factor in improving the quality of religious services at KUA Padang Utara District.